Integration and Applications in Economic Dynamics (Open Herald: Periodical of Methodical Research, 2023)
In a dynamic economics model, the basic objective is the identification of the time path of the variable on the basis of its rate of change. For example, national income y of a country changes overtime. To see the rate of change we need to see its change with respect to time and to find the time path followed by y . Thus, if we know the derivative dy dt , it will be possible to get onto the function like y y t = ( ) through the technique of integration which happens to be opposite of the process of differentiation. We will return to this process after a while